1992
DOI: 10.1002/gcc.2870050209
|View full text |Cite
|
Sign up to set email alerts
|

Viral integration and fragile sites in human papillomavirus‐lmmortalized human keratinocyte cell lines

Abstract: Human papillomavirus (HPV) types 16 and 18 integration sites were mapped in six HPV-immortalized human keratinocyte cell lines by fluorescence in situ hybridization (FISH). Mapping of HPV sequences in these cell lines revealed that HPV integration varied in copy number and location but that integration sites were stable over extended passages in culture. Integration occurred at different sites throughout the genome and did not correspond to the location of specific cellular genes. However, integration sites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 34 publications
2
61
0
3
Order By: Relevance
“…There was a high correlation between the individual locations of HPV integration sites and fragile sites in the genome since 40 of 57 mapped HPV integration sites were found near fragile sites. These observations con®rm data of other investigators, who have reported HPV integration sites near fragile sites in various cell lines and very few cervical carcinoma samples (Popescu et al, 1987;Smith et al, 1992;Thorland et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…There was a high correlation between the individual locations of HPV integration sites and fragile sites in the genome since 40 of 57 mapped HPV integration sites were found near fragile sites. These observations con®rm data of other investigators, who have reported HPV integration sites near fragile sites in various cell lines and very few cervical carcinoma samples (Popescu et al, 1987;Smith et al, 1992;Thorland et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Smith et al (1992) reported that HPV integration sites were consistent with integration near or within known fragile sites in ®ve of six HPVimmortalized keratinocyte cell lines. Wilke et al (1996) have shown that a region of frequent breakage within FRA3B coincided with a previously characterized site of HPV16 integration in a primary cervical carcinoma.…”
Section: Discussionmentioning
confidence: 85%
“…Unlike multicellular organisms, the early two-cell embryo either had only two copies of the genome that became disrupted by the HPV DNA or it lacked the necessary repair mechanism to correct for the integrated HPV DNA. The sites for HPV DNA integration into the host genome have been reported to be near oncogenes (27) causing transformation of cells, or at the chromosomal fragile site (28)(29)(30)(31)(32) at 3p14 (31,33) and the FRA8C site at 8q24 (34) resulting in gene interruption and loss of chromosome heterozygosity (24,35). Indirect evidence linking HPV infection and embryo demise would be the prevalence of HPV infection in the infertile population.…”
Section: Discussionmentioning
confidence: 99%